Insurgent multiplicities. (July 2023) - Olson, Kevin
My discussion of Massimiliano Tomba's Insurgent Universality focuses on intertwined themes of historicism, normativity, and revolution that I find particularly generative. By drawing them together I hope to trace out important parts of the book's conceptual infrastructure, especially the way it uses insurgent moments of the past to conceptualize alternative modernities. My particular focus is the sense in which Tomba hopes to "reactivate" important aspects of past insurgent moments. In the end, I argue that his arguments actually go much farther to displace universalism than he credits them. Agreeing with the spirit of Tomba's work rather than its letter, I believe that he provides us with good grounds to focus on insurgent multiplicities rather than insurgent "universality."